Review: Tepung Telur Ayam: Nilai Gizi, Sifat Fungsional dan Manfaat - Z. Wulandari; I. I. Arief (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2022)
Eggs are an almost perfect source of animal protein. Commercial chicken eggs are a perfect food that contains nutrients such as protein (12.8 %) and fat (11.8 %). In 100 grams of whole eggs also contain vitamin A of 327.0 IU and minerals of 256.0 mg. Eggs contain high-quality protein because they have a complete composition of essential amino acids and have a high biological value, which is 100 %. The high content of water, fat and protein in eggs make this food as a good medium for bacterial growth so that their shelf life is quite short. Drying eggs into powder offers many advantages, including ease of storage, distribution, protection against microbial growth (low water activity), reduced weight per volume of whole eggs, longer shelf life. The use of egg powder as an additive to other food products is easier than using fresh eggs. The purpose of this review is to study the nutritional characteristics, functional properties and benefits of egg flour. The nutritional value and functional properties of egg powder, egg white powder and egg yolk powder can still provide maximum results both for raw material products or as food additives. The use of egg powder will facilitate industry, especially medium and large scale industries in handling, packaging, storage and processing compared to use with fresh eggs.